Incidence of iron deficiency and iron deficient anemia in elite runners and triathletes - Coates, A.; Mountjoy, M.; Burr, J. (Clinical Journal of Sport Medicine, 2017)
Objective: To assess the incidence of iron deficiency (ID), and iron deficient anemia (IDA) within a cohort of highly trained runners and triathletes, and to examine the association of oral iron supplementation history with serum ferritin (sFe) and hemoglobin (Hb) concentrations.